Quercetin alleviates ulcerative colitis through inhibiting CXCL8-CXCR1/2 axis: a network and transcriptome analysis - Jiang, Zhangyu; Yan, Mingjuan; Qin, Yanmi; Liu, Zhenglin; Duan, Yilin; Wang, Yingju; Zhang, Ruisen; Lin, Wenjia; Li, Yanwu; Xie, Tian; Ke, Junyu (Frontiers in Pharmacology, 2024)
Introduction Ulcerative colitis (UC) is a chronic inflammatory condition of the intestinal tract in which mucosal healing is a crucial measure of therapeutic efficacy. Quercetin, a flavonoid prevalent in various foods and traditional Chinese medicines, exhibits notable pharmacological properties, including antioxidant and anti-inflammatory activities. Consequently, it warrants investigation to determine its potential therapeutic effects on UC. The objective of this study was to investigate the effects and underlying mechanisms of quercetin in a murine model of UC. Methods A comprehensive approach integrating network predictions with transcriptomic analyses was employed to identify the potential targets and enriched pathways associated with quercetin in UC. Subsequently, the effects of quercetin on pathological morphology, inflammatory mediators, and mucosal barrier-associated proteins, as well as the identified potential targets and enriched pathways, were systematically investigated in a murine model of dextran sulfate sodium (DSS)-induced UC. Results Network analyses identified CXCL8 and its receptors, CXCR1 and CXCR2, as primary target genes for therapeutic intervention in UC. Further validation through transcriptomic analysis and immunofluorescence staining demonstrated significant upregulation of the CXCL8-CXCR1/2 axis in the intestinal tissues of patients with UC. Experimental investigations in animal models have shown that quercetin markedly alleviates DSS-induced symptoms in mice. This effect includes the restoration of colonic crypt architecture, normalization of goblet cell structure and density, reduction of inflammatory cell infiltration, and decreased concentrations of inflammatory mediators. Quercetin enhanced the expression of tight junction (TJ) proteins, including ZO-1, MUC2 (Mucin 2), and occludin, thereby preserving the integrity of the intestinal mucosal barrier. Additionally, it significantly diminished the levels of IL-17A, NF-κB, CXCL8, CXCR1, and CXCR2 in the colonic tissues of mice with UC. Discussion The ameliorative effects of quercetin on colon tissue damage in DSS-induced UC mice were significant, possibly due to its ability to inhibit the CXCL8-CXCR1/2 signaling axis. These findings provide a solid foundation for the clinical application and pharmaceutical advancement of quercetin.